Gambaran Sedimen Urin Kristal Kalsium Oksalat pada Pengonsumsi Air Sumur Bor dan Air Galon Isi Ulang di Desa Kendalsari RT 04 RW 05 Kecamatan Petarukan Kabupaten Pemalang - Faizal Iqbaludin; Fitrianingsih Fitrianingsih (Jurnal Medika Husada, 2024)
Sources of drinking water that can be used by humans as drinking water needs are springs, surface water, ground water (drilled wells and dug wells) and rainwater. In Kendalsari Village, the water consumed contains lime and scale. This can stain porcelain and laundry equipment. If consumed continuously, it is certainly very dangerous for health. To determine the percentage of urinary sediment crystals of calcium oxalate in consumers of bore well water and refill gallons of water in Kendalsari Village, RT 04 RW 05, Petarukan District, Pemalang Regency. The type of research used is descriptive. The number of samples obtained using the simple random sampling method consisted of 25 samples of people consuming bore well water and 25 samples of people consuming refill gallons of water. Consumption of borehole water, positive results of calcium oxalate crystals were obtained by 9 (36%) positive samples 1 totaling 3 (12%) samples, positive 2 totaling 1 (4%) and positive 3 totaling 5 (20%) while negative results 16 (64%) of the samples and the consumption of refill gallons of water obtained positive results for calcium oxalate crystals as many as 14 (56%) positive samples 1 totaling 3 (12%) samples, positive 2 totaling 6 (24%) and positive 3 totaling 5 ( 20%) while the results were negative in 11 (44%) samples. Consuming bore well water obtained positive samples of calcium oxalate crystals totaling 9 (36%) samples while negative samples of calcium oxalate crystals totaling 16 (64%) samples and consuming gallons of refill water obtained positive samples of calcium oxalate crystals totaling 14 (56%) of the sample while the results of negative samples of calcium oxalate crystals amounted to 11 (44%) samples.